The charge al-Ghazali philosophers in a takfira and al-Farabi (Journal of Philosophy Culture and Political Science, 2018)
This article considers the role and functions of Islamic philosophy in medieval scientific system from a position of spiritual, practical and world outlook. Significant differences and contradictions of scientific and beliefs doctrine which were created during development of Islamic culture are shown. The article considered philosophical ideas of authoritative Islamic scientists such as al-Farabi and al-Ghazali, who developed the ideas of human and divine knowledge in Islamic science, philosophy and religion.There is also a comparative method that helps al-Ghazali to analyze the main three problems and, therefore, allowed him to accuse the philosophers of kufra: 1. God knows the general and does not know the special; 2. The genesis of the Universe; 3 Rebirth of the human being. There are also the proofs of al-Farabi on some issues that have been put by al-Ghazali in his «The Incoherence of the Philosophers».Key words: Islamic philosophy, al-Farabi, al-Ghazali, The Incoherence of the Philosophers, akl, nakl, kulli, ghuzi.